Київська ротонда і питання її атрибуції - Висоцький, С.О. (Археологія, 1994)
У статті розглядаються питання, пов'язані з вивченням Київської ротонди. Будова визначається автором як православна Катерининська церква, руїни якої позначені на плані Києва 1695 р. В статье на основании материалов раскопок Киевской ротонды и изучения письменных источников опровергается мнение, что это был католический костел Девы Марии или светская постройка. Автор приходит к выводу, что Киевская ротонда и руины церкви Екатерины, показанные на плане Киева 1695 г. — одно и то же сооружение, о восстановлении которого, наряду с Трехсвятительской церковью, хлопотали киевские митрополиты перед русским царем. Это является убедительным доказательством того, что церковь Екатерины была православным храмом. Relics found during excavation of the Kiev rotunda and data from the published sources give grounds to reject the existing opinion that it was Catholic church of Virgin Maria or a secular building. The author comes to the conclusion that the Kiev rotunda and ruins of St. Ekaterina church shown in the plan of Kiev of 1695 are one and the same building and Kiev metropolitans solicited the Russian tsar about its restoration as well as about restoration of the Trekhsvyatitelskaya church. This fact convincingly proves that St. Ekaterina church was an Orthodox temple.